Implementasi Sakti Dengan Pendekatan Technology Acceptance Model - Willi Williyanto; Dwi Martani Martani (Coopetition : Jurnal Ilmiah Manajemen, 2023)
At present the development of data systems has become a significant need for all organizations, including the government, in increasing the effectiveness and efficiency of performance processes in providing quality data as a form of accountability and transparency to the public. The Directorate General of Treasury (Directorate General of Treasury) in order to improve quality and facilitate the process of managing public finances, is constantly improving the data technology that has been provided. The Institutional Level Financial Application System (SAKTI) developed by the Directorate General of Treasury is an integrated solution for managing state finances at the Work Unit level. So that the management of state finances is expected to be easier, faster, and more accurate. SAKTI is an application that integrates applications in Satker into one application, so users or users do not need to access many applications in managing state finances. Since 2015, SAKTI has undergone piloting sessions to ensure that SAKTI is suitable for use by all work units throughout Indonesia and applies to all ministries and agencies in Indonesia since 2021.